Photocatalytic removal of food colorant using NiO/CuO heterojunction nanomaterials. (September 2022) - Gnanasekaran, Lalitha; Santhamoorthy, Madhappan; Naushad, Mu.; ALOthman, Zeid A.; Soto-Moscoso, Matias; Show, Pau Loke; Khoo, Kuan Shiong
Abstract: In recent days, the existence of several food colorants has an impact on human health issue that may induce major carcinogenic effects. Therefore, the removal of food colorants must be made in accordance with the necessity of health awareness in life. Photocatalyst treatment using semiconductors shows a promising way to solve these issues. In this relation, this paper presents the novel nanoflower shaped NiO/CuO (0.9:0.1 M and 0.5:0.5 M) photocatalysts developed via co-precipitation method for the destruction of methyl orange (MO) as a model food colorant under visible light irradiation. The X-ray diffraction result proposed that the composite catalysts consist of mixed heterostructures (cubic and monoclinic) with no other impurities. From the images of transmission electron microscope, the catalyst presents nano spherical and cubical mixed morphologies. Besides, NiO/CuO (0.5:0.5 M) catalyst exhibits agglomeration due to the highly contented CuO. The Energy Dispersive X-ray spectra gave the elemental configuration without other impurity traces. The Brunauer-Emmett-Teller surface area of NiO/CuO (0.9:0.1 M) catalyst occupies higher surface area. Unfortunately, NiO/CuO (0.5:0.5 M) sample has lower surface area due to the agglomerated particles. The UV–vis spectra confirmed that the absorption of the catalyst lies in higher wavelength region occupying small band gap. Moreover, the visible light activity of the catalysts showed 75.3% (0.9:0.1 M) and 40.2% (0.5:0.5 M) degrading efficiencies. At the end, the highly efficient catalyst was experienced photocatalytic activity upto 5 repeated runs and the efficiency remained the same. Therefore, the catalyst NiO/CuO (0.9:0.1 M) has prompted the successful degradation of MO food colorant under visible light. Highlights: Removal of food colorant using the prepared p-n catalyst under visible light. Larger surface area and high active sites help for enhancement of food colorant removal. p-n junction induces drift current to boost the charge carriers.